The Impact of Gendered Language in Bangladeshi Law and Policy:: Critical Analysis - Sabiha, Salma (The Jahangirnagar Review, 2025)
Gendered language refers to terms, expressions, or other language components that are not included in the Bangladeshi legal system but that either directly or indirectly allude to gender discrimination or distinction. The aim of this study was to investigate the incidents of gendered language used in the Bangladeshi laws and policies and identify the types of gendered language on the objectives of goals for gender equity. This is a qualitative research method by assessing legal documents, policy papers and case studies through the critical discourse analysis. Analysis of the result proves that gender stereotyped language is visible in the variety of legal fields but specifically in family, labor and criminal legal fields. Such problems are commonly reflected in the traditional gender roles for which this linguistic bias is inclined towards hampering the interpretation of laws and application thereof to the detriment of the women and other minority categories. This study finds, among other things, that these continued gendering, despite them being today’s official texts, are owing to forces of prevailing patriarchal, religious and colonial influence today. But this prejudice of English language is a bit more than meets the eye as it may have potential to lead to gender imbalance and even justice. Lack of interest in legal protection on part of the women may be a result of the presence of sexism in laws and policies that inflict on their status as inferior right holders within the society. The study recommends creating guidelines for gender sensitive legal droughting, conducting a thorough examination of current laws and regulations to replace gender biased terminology with gender neutral ones and starting public awareness campaigns. Finally, the study concludes that incorporating gender neutral language in the laws and policies is imperative to advocate for gender equality and social justice in the country of Bangladesh. Future research directions include exploring the practical implementation of gender-neutral language in legal contexts and conducting comparative studies with other South Asian countries.